Variability in measurement of swimming forces: A meta-analysis of passive and active drag - Havriluk, R. (Research Quarterly for Exercise and Sport, 2007)
An analysis was conducted to identify sources of true and error variance in measuring swimming drag force to draw valid conclusions about performance factor effects. Passive drag studies were grouped according to methodological differences: tow line in pool, tow line in flume, and carriage in tow tank. Active drag studies were grouped according to the theoretical basis: added and/or subtracted drag (AAS), added drag with equal power assumption (AAE), and no added drag (ANA). Data from 36 studies were examined using frequency distributions and meta-analytic procedures. It was concluded that two active methods (AAE and ANA) had sources of systematic error and that one active method (AAS) measured an effect that was different from that measured by passive methods. Consistency in drag coefficient (Cd) values across all three passive methods made it possible to determine the effects of performance factors.